Clinical and Epidemiological Determinants of Lower Respiratory Tract Infections in Hospitalized Pediatric Patients - Mohammadreza Mirkarimi; Mohsen Alisamir; Salar Saraf; Solmaz Heidari; Shahriar Barouti; Shooka Mohammadi (Hindawi Limited, 2020)
Background. Lower respiratory tract infection (LRTI) is the main cause of pediatric mortality and morbidity in low- and middle-income countries. Purpose. This study was carried out to determine the clinical and epidemiological characteristics of children with LRTI. Method. A retrospective study was conducted on all pediatric patients who were hospitalized due to LRTI in Abuzar Hospital (Ahvaz, Iran) during one year. Incomplete medical records and children who were treated on an outpatient basis, as well as infants younger than 1 month of age, were excluded. The patients were evaluated in terms of epidemiological, clinical, and paraclinical characteristics. Results. A total of 303 hospitalized children and infants were identified. Their mean age was 29.09±38.96 months (range 1 month-15 years), and 59.4% of them were males. The highest frequency of patients was at the age below one year (50.8%, n=154). Pneumonia and bronchitis were the most common LRTIs. Respiratory (54.6%) and neurological (21.6%) diseases were the most prevalent underlying medical conditions. Admission was more common in winter (n=120, 39.6%) and spring (n=79, 26.1%). The mean length of stay (LOS) in the hospital was 8.2±5.5 days, and the overall mortality rate was 11.6%. In addition, 65 patients were severely underweight and 271 patients were malnourished. Moreover, there was a significant association between mortality and disease diagnosis (p<0.05). Furthermore, there was a significant association between having an underlying disease and consanguineous parents (p<0.01), as well as the frequency of hospitalization (p<0.001). Conclusion. Additional studies are required to determine factors contributing to disease severity among children with LRTI to develop appropriate preventive and therapeutic strategies.